How do Service Quality, Value, Pleasure, and Satisfaction Create Loyalty to Smart Dockless Bike-Sharing Systems? - Liu, Yong (2020)
Purpose – The purpose of this research is to investigate which factors influence users’ loyalty to smart dockless bike-sharing systems (DBSS).  Design/methodology/approach – A sample of 374 subjects who had previously experienced smart DBSS was obtained and the partial least squares (PLS) method was performed to analyze the measurement and structural models.  Findings – The results indicated that customer loyalty was the final construct produced by perceived green value, customer satisfaction, and perceived pleasure, which were found to be partial mediators between service quality and customer loyalty.   Originality/value – This study (1) provides a new perspective from which to examine consumer loyalty behavior in a smart DBSS context, (2) it identifies the role of service quality as an important stimulus, (3) it confirms that perceived pleasure not only has an effect on customer loyalty, but also acts as an excellent mediator, and (4) it provides empirical evidence for smart DBSS providers to enhance the adoption of green transport and to strengthen customer loyalty to smart DBSS.